Analisis Terminologi Fashion di Korea dalam Channel Youtube Bertema Fashion - Mushonif, Mushonif; Triarisanti, Risa; Azizah, Asma (Syntax Literate, 2025)
This research analyzes Korean fashion terminology in fashion-themed YouTube channels. It aims to classify, identify the word-formation processes, and explain the semantic functions of fashion terms used in Korean. Using qualitative descriptive methods, data were collected from various YouTube videos focusing on Korean fashion. The analysis was conducted using morphological theories by Go & Goo and semantic analysis by Leech. A total of 246 terms were identified and classified based on categories from the Fashionpedia book, including Apparel, Detail, Accessories, Textile, Manufacturing, Body & Beauty, and Measurement & Care. The results show that most terms originate from foreign words (외래어), Chinese loanwords (한자어), and native Korean (고유어), with the Manufacturing category dominating the dataset. The word formation processes include single words, compounds, derivation, and borrowing. This study reveals the linguistic diversity and cultural adaptation reflected in Korean fashion terminology and emphasizes the importance of understanding these terms in both industry and daily contexts.